Renewable Energy and Economic Growth in Indonesia: Evidence from VECM Causality - Alfisyahri, Nuriah; Abdi Prawira, Ilham; Burhanuddin, Burhanuddin; FA, Jalaluddin; Harmain, Irfan; Burhanuddin (Sustainability (STPP) Theory, Practice and Policy, 2022)
Attention to sustainable development globally has accelerated the focus on renewable energy consumption in recent decades. This study discusses the causality between carbon dioxide emissions, renewable energy consumption-hydropower, renewable energy consumption-geothermal, biomass, and other sources on economic growth. Using the VECM and Granger Causality methods to see the relationship between variables in the long term and short term. This study uses time series data from 1990-2020 in Indonesia. The results of the study are that carbon dioxide emissions and renewable energy consumption-hydropower are significantly positive for economic growth in the long and short term, while renewable energy consumption-geothermal, biomass, and other sources are significantly negative for economic growth. In terms of causality, in the long term, all variables have a one-way causal relationship, while in the short term, carbon dioxide emissions and economic growth and renewable energy consumption-geothermal, biomass, and other and economic growth have an alternating causality relationship.